Simple Fabrication of Carbon Nanotubes from Ethanol using an Ultrasonic Spray Pyrolysis - Abdullah, Mikrajuddin; Iskandar, Ferry; Okuyama, Kikuo (ITB Journal Publisher, LPPM ITB, 2004)
Carbon nanotubes of diameter (20â100 nm) are synthesized by pyrolyzing a sprayed solution of Fe(C5H5)2 and C2H5OH in an Ar atmosphere at relatively low temperatures (around 800 oC). The tubular structures consist of highly crystalline nested graphene cylinders (<200 concentric tubes). Tube diameter can be controlled by varying the furnace temperature, carrier gas flow rate and the Fe:C ratio within the precursor solution. This low cost route for the synthesis of carbon nanotubes is advantageous due the low pyrolytic temperature, safety, processable in atmospheric pressure, and scalable.